The Role of Aldosterone in OSA and OSA-Related Hypertension - Wang, Yi; Li, Chuan Xiang; Lin, Ying Ni; Zhang, Li Yue; Li, Shi Qi; Zhang, Liu; Yan, Ya Ru; Lu, Fang Ying; Li, Ning; Li, Qing Yun (Frontiers in Endocrinology, 2022)
Obstructive sleep apnea (OSA) is regarded as an independent risk factor for hypertension. The possible mechanism includes oxidative stress, endothelial injury, sympathetic excitement, and renin-angiotensin-aldosterone system activation, etc. Clinical studies have found that there is high coexistence of OSA and primary aldosteronism in patients with hypertension, and that elevated aldosterone levels are independently associated with OSA severity in resistant hypertension. The underlying mechanism is that aldosterone excess can exacerbate OSA through increasing overnight fluid shift and affecting the mass and function of upper airway muscles during sleep period. Thus, bidirectional influence between OSA and aldosterone exists and contributes to hypertension in OSA patients, especially resistant hypertension.